Pengaruh Media Diorama terhadap Motivasi Belajar Siswa pada Tema Ekosistem Kelas IV di Sekolah Dasar Negeri 105336 Rantau Panjang - Anggrayni Wibowo Pohan; Nizmi Putri; Layil Safitri (Medan Resource Center, 2026)
This study was motivated by the need for concrete instructional media to facilitate elementary students' understanding of abstract concepts related to ecosystem learning, particularly food chains. It investigates how the use of diorama media influences students' learning motivation and examines the differences in motivation before and after its implementation. The study employed a descriptive qualitative approach by exploring students' and teachers' experiences through classroom observations, semi-structured interviews, and learning achievement tests as supporting data. The findings indicate that diorama media substantially enhanced students' learning motivation, with 80% of students demonstrating high levels of enthusiasm, active participation, and greater willingness to ask questions during the learning process. These qualitative findings were reinforced by quantitative evidence, including an increase in the average learning score from 54.5 to 83.5, an N-Gain score of 0.64 (moderate category), and 100% learning mastery. The study concludes that diorama media serves as an effective concrete instructional tool for strengthening students' learning motivation while fostering a deeper conceptual understanding of ecosystem topics in elementary education.